P511 Early prediction of steroid failure in acute severe ulcerative colitis. (16th January 2018) - Choy, M C; Boyd, K; Burder, R; Gorelik, A; Nallas, R; Horvath, J; Lam, Q; Crinis, N; Van Langenberg, D; Sparrow, M; Connell, W; Visvanathan, K; et al.
Abstract: Background: Acute severe ulcerative colitis (ASUC) is a medical emergency that requires prompt assessment and judicious management. IV corticosteroids are first-line therapy, but a significant proportion who do not improve after 3–7 days require salvage treatment or surgery. Management decisions are conventionally based on the Oxford criteria 1 though recent data suggest that an Ulcerative Colitis Endoscopic Index of Severity (UCEIS) >6 and faecal calprotectin (FC) >1000 μg/g at Day 3 are markers of steroid failure. We report the results of a study which examined the association of steroid response with clinical activity, biomarkers and endoscopic findings at admission. Methods: A prospective cohort of inpatients with ASUC treated with IV steroids were recruited from 4 Australian hospitals and underwent clinical and endoscopic assessment. Bloods were assessed prior to IV steroids and FC prior to endoscopy. Steroid failure was defined if patients met the Oxford Day 3 or 7 criteria. Steroid responders did not meet these criteria. Statistical comparisons were made using Mann–Whitney U and Fisher's test. Area under the receiver operating curve analysis (AUROC) was performed to assess predictors of treatment. Results: Forty-one patients were enrolled (18 female; median age 33.9 years (Q1–3 = 24.5–42.7)). Ten patients were steroid responsive; 31 were steroid refractory and received infliximab salvage therapy. Prior diagnosis of colitis, disease/flare duration or therapy history were not associated with outcome. The Lichtiger score, endoscopic activity, CRP, albumin and FC were significantly different between steroid failures and responders (Table 1). FC was predictive of steroid failure (AUROC = 0.89) with an optimal cut-off of 1395 μg/g (sensitivity of 89%, specificity of 63%, PPV of 67% and NPV 67%). CRP/Albumin ratio (CAR) was predictive of steroid failure (AUROC 0.89) with an optimal cut-off of 1.34 (sensitivity of 85%, specificity of 87%, PPV of 93% and NPV of 67%). The combination of FC >1395 μg/g and CAR >1.34 was strongly predictive of steroid failure (sensitivity 79% specificity 100% PPV 100% and NPV 62.5%). Conclusions: Early faecal and blood biomarkers are useful in stratifying patients at risk of steroid failure. All patients with an FC >1395 μg/g and CAR >1.34 were steroid refractory. Implementation of such risk factors may allow early identification of patients for whom steroid therapy is likely to be futile and expedite the initiation of salvage therapy. Reference: 1. Travis SP, Farrant JM, Ricketts C, et al. Predicting outcome in severe ulcerative colitis. Gut, 1996.